2021
DOI: 10.1002/anie.202010951
|View full text |Cite
|
Sign up to set email alerts
|

A Cisplatin‐Selective Fluorescent Probe for Real‐Time Monitoring of Mitochondrial Platinum Accumulation in Living Cells

Abstract: Mitochondria have emerged as important targets for cisplatin in cancer therapy. Apart from cisplatin, anticancer Pt complexes based on similar scaffolds have also been developed to target mitochondria. Yet cellular processing of cisplatin or these mitochondria‐targeting Pt analogues remained unexplored, largely due to a lack of tools capable of probing these Pt drugs within an intracellular environment. We developed the first mitochondria‐targeted fluorescent probe for real‐time monitoring of Pt accumulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Interestingly, we also found indications that the compound might be metabolized (intra-and/or extracellularly) to a DACH-free platinum species. Noteworthy, there are only a few studies so far, which address the intracellular or even intratumoral drug distribution of metal-based drugs or their nanoformulations in vitro 44,45 or in vivo. 42…”
Section: Kp2156 Enters Cancer Cells In Vivo Via the Endo-/lysosomal Pathwaymentioning
confidence: 99%
“…Interestingly, we also found indications that the compound might be metabolized (intra-and/or extracellularly) to a DACH-free platinum species. Noteworthy, there are only a few studies so far, which address the intracellular or even intratumoral drug distribution of metal-based drugs or their nanoformulations in vitro 44,45 or in vivo. 42…”
Section: Kp2156 Enters Cancer Cells In Vivo Via the Endo-/lysosomal Pathwaymentioning
confidence: 99%
“…There is still an intense research interest in developing novel Pt‐based therapeutics for cancer treatment four decades after the approval of cisplatin [4c,5a,9] . A primary challenge is to improve patient benefit by reducing damage to normal tissues resulting in nausea and hair loss among other side effects.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple therapeutic and/or diagnostic modalities have been integrated to try and achieve synergistic and spatiotemporal treatment [19] . Aside from nanomaterial assembly, carefully designed Pt‐based complexes can also be used to achieve fine‐tuning of the drug‐biomolecule interaction [4c,e,f,20] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin accumulates in the mitochondria of renal PTCs and forms crosslinks with mtDNA and proteins [25]. Recent evidence using a platinum selective fluorescent probe has shown that the Cytochrome c oxidase copper chaperone 17 (COX17), a mitochondrial intermembrane enzyme involved in copper transfer [61], mediated the mitochondrial internalization of cisplatin in HeLa cells [62], suggesting a mechanism by which mitotoxicity may occur [63].…”
Section: Cisplatin Induced Mitochondrial Dysfunction In the Kidneymentioning
confidence: 99%